PENGARUH FILLER ABU AMPAS TEBU (AAT) DENGAN BAHAN PENGIKAT ASPAL PEN 60/70 PADA CAMPURAN LASTON AC-WC - Febrina Dian Kurniasari; Sofyan M. Saleh; Sugiarto Sugiarto (Prodi Magister Teknik Sipil Unsyiah, 2018)
Cause of occurrence damage and decrease of road pavement strength is low strength and durability in a mixed layer (AC-WC). To overcome this problem, it is necessary to improve the quality of road pavement in aggregate, filler, and asphalt composition. Filler serves to isolate the cavities between the aggregate particles so as to increase the density of the mixture. In general, the filler of stone ash has been used. However, it is important to find for other alternative materials which utilizing waste materials such as dregs of bagasse. The content of silica (SiO2) in ashes of bagasse is very high, 42.47%, thus it is expected to improve the quality of asphalt mixture. This study aims to determine the effect of using ashes of bagasse over the characteristics of mixed laston layer (AC-WC) with the addition of bagasse ash from 0%, 25%, 50%, 75% and 100%. This study refers to the 2010 Bina Marga Specification Revision 3 Year 2014. The results show that the addition of ash of bagasse has increased stability value. In general, the characteristic values that meet the requirements are found in the composition of 50% filler ash of bagasse asphalt at 5.87%, VIM value of 4.61%, VMA 18.41%, flow 3.17 mm and stability is 1344 , 04 kg.